Carnivory in the Alpine marmot (Marmota marmota): An underestimated phenomenon?. Issue 2 (4th March 2021) - Böhm, Christiane; Landmann, Armin
Abstract : Alpine marmots are thought to be herbivores but to be selective regarding food choice with focus on plant material rich in proteins and fatty acids. Carnivorism has been occasionally observed in Alpine marmots in captivity as well as in the wild but has been considered rare and opportunistic. Here we report additional cases from zoos and the wild which indicate that Alpine marmots not only readily accept meat as food but are also capable of actively preying on vertebrates. We speculate that the intake of protein and fatty acids from animal tissues, whenever occasions arise, may have a nutritional value and could thus be adaptive for Alpine marmots.